Two new endemic Hawai‘ian Lepidoptera: a new species of Pseudoschrankia (Erebidae) from O‘ahu, and a new species of Thyrocopa (Xyloryctidae) from Moloka‘i - Medeiros, Matthew J (Zootaxa, 2015)
Two new endemic Hawai‘ian Lepidoptera species are herein described. The first, Pseudoschrankia brevipalpis sp. nov., is a pollinator of the rare endemic plant Schiedea kaalae Wawra. The second, Thyrocopa keliae sp. nov., is endemic to Moloka‘i island. Observations of undescribed parasitic mites that attack Hawai‘ian Lepidoptera are presented as well.